Correlation between isothermal crystallization and morphological/rheological properties of bimodal polyethylene/carbon black systems. Issue 3 (26th October 2018) - Sarafpour, Amirhosein; Pircheraghi, Gholamreza; Rashedi, Reza; Afzali, Kamal
Abstract : Studying factors that can cause changes in microstructure and different properties of polyethylene pipe materials are important to better predict pipe behavior. In this study, bimodal polyethylene compounds were prepared using three different grades of carbon black (CB) concentrated dispersion to investigate the role of CB carrier's molecular weight on microstructure, crystallization, and rheological properties of samples. Isothermal crystallization and Avrami equation showed the nucleating effect of CB and a decrease in overall crystallinity caused by CB particles, with no major effect of carrier molecular weight on polyethylene unit cell parameters, confirmed with WAXD measurements. Similarly, it was revealed by FE‐SEM images that the higher the molecular weight of CB carrier, the lower the compound's ability to form three‐dimensional spherulites. The melt miscibility of samples was evaluated based on rheological properties, while a correlation between rheological parameters and Avrami index was observed. It is concluded that a small amount of CB carrier can change the balanced molecular weight distribution of bimodal polyethylene resin and strongly influence crystallization behavior and microstructure development of samples. The microstructure of bimodal black polyethylene compounds can determine their properties, especially long‐term performance like resistance to slow crack growth. Abstract : Evaluating the effect of carbon black concentrated dispersion in bimodal polyethylene can be of great importance, as it can have a significant influence on the microstructure and properties of compounds. It can also possibly determine its long‐term performance, an issue rarely discussed in literature. In this work, the crystallization behavior, rheological properties and microstructure of black compounds are studied and the effects of carbon black polymer carrier on properties of the base polyethylene material are evaluated.